The Boon and Bane of Blockchain: Getting the Governance Right. (May 2022) - Goldsby, Curtis; Hanisch, Marvin
Countless enterprise blockchains fail to live up to high expectations, often because the supporting governance structures are insufficiently established or have become stagnant. Based on interviews with 153 blockchain executives and an analysis of publicly documented use cases, this article offers a guide for blockchain scholars and practitioners. Its framework highlights the coordination and control challenges that exist in blockchain governance contexts and presents four generic governance modes to address them: chief, clan, custodian, and consortium. Managers can use these governance modes as a basis for four strategic moves (connecting, isolating, loosening, and tightening) to navigate blockchain governance challenges.